2021
DOI: 10.1002/jez.2555
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological damage and stress‐ and immune‐related genes' expression in the intestine of common carp, Cyprinus carpio exposed to copper and polyvinyl chloride microparticle

Abstract: The present study aimed at assessing the singular and combined effects of water copper and polyvinyl chloride microplastic (MPVC) on intestinal copper accumulation, histopathological damage, and stress‐/immune‐related genes' expression in common carp, Cyprinus carpio. Four groups of fish were maintained in triplicate: control (kept in clean water), Cu (exposed to 0.25 mg/L of copper), MPVC (exposed to 0.5 mg/L of MPVC), and Cu‐MPVC (exposed to 0.25 mg/L of copper + 0.5 mg/L of MPVC). After 14‐day exposure, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 57 publications
(69 reference statements)
1
9
0
Order By: Relevance
“…Role of TEM in NP research is unquestionable but its impact on aquatic system needs to be assessed carefully (Mazzaglia et al, 2018; Mineo, Faggio, Micali, Scamporrino, & Villari, 2014; Mühlfeld et al, 2007). Nanoplastics are obtained after degradation of plastic and have been illustrated to possess negative impact in fish upon its accumulation (Hoseini et al, 2021). The study conducted on mice evidenced ultrastructural change in the macrophage line upon exposure to carbon nanotubes (Di Giorgio et al, 2011).…”
Section: Em In Toxicity Assessmentmentioning
confidence: 99%
“…Role of TEM in NP research is unquestionable but its impact on aquatic system needs to be assessed carefully (Mazzaglia et al, 2018; Mineo, Faggio, Micali, Scamporrino, & Villari, 2014; Mühlfeld et al, 2007). Nanoplastics are obtained after degradation of plastic and have been illustrated to possess negative impact in fish upon its accumulation (Hoseini et al, 2021). The study conducted on mice evidenced ultrastructural change in the macrophage line upon exposure to carbon nanotubes (Di Giorgio et al, 2011).…”
Section: Em In Toxicity Assessmentmentioning
confidence: 99%
“…Damaged DNA, oxidative stress, histopathology, and changes in the blood biochemical parameters are reported in the finfish and shellfish exposed to MPs [7,10,13,14]. Moreover, exposure to MPs could induce immunotoxicity and change the intestinal microbiota [15]. MPs can act like Trojan horses that can transit various environmental contaminations [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…These act as absorbers of other chemical and biological pollutants by virtue of their physical and chemical properties. Heavy metals are known pollutants that MPs can carry in water ecosystems [15,[20][21][22][23]. Thus, MPs can affect the toxicity and bioavailability of other xenobiotics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…And Sheir et al indicated that Cd could inhibit the innate immune response of shellfish (24). Meanwhile, Cu has been reported in previous research to significantly inhibit the functions of immune cells, and inhibit lysozyme activity and phagocytosis, resulting in immune system disorders (25)(26)(27). Hitherto, the effects of Cd and Cu coexposure on immune response mechanisms have been rarely studied in marine organisms and have not been studied in cephalopods.…”
Section: Introductionmentioning
confidence: 99%